2004
DOI: 10.1002/j.2168-9830.2004.tb00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Influencing Engineering Student Graduation: A Longitudinal and Cross‐Institutional Study

Abstract: Pre‐existing factors are quantitatively evaluated as to their impact on engineering student success. This study uses a database of all engineering students at nine institutions from 1987 through 2002 (a total of 87,167 engineering students) and focuses on graduation in any of the engineering disciplines. We report graduation rate as a function of years since matriculation, and determine the typical time‐to‐graduation. A multiple logistic regression model is fitted to each institution's data to explore the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
197
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(219 citation statements)
references
References 5 publications
14
197
1
Order By: Relevance
“…Nichols et al made use of ordinal regression for analyzing the data obtained from 187questionnaires returned by distance education students; the results showed that among four sets of attributions (namely computer usage attitudes, learning motivation, perception of satisfaction and previous academic performance), only previous academic performance exhibited a strong correlation with dropout [21]. Research by Zhang et al used multivariate regression to analyze the data of 57,549 students from nine universities: results showed that demographic attributions such as gender, ethnicity and nationality attribution are significantly correlated to dropping out [22]. Another logistic regression study conducted by Doherty analyzed the data of 10,466 students in the educational institution information system; results showed that the students' demographic attributions, learning methods, and curriculum interaction were correlated to dropping out [23].…”
Section: B Empirical Researchmentioning
confidence: 99%
“…Nichols et al made use of ordinal regression for analyzing the data obtained from 187questionnaires returned by distance education students; the results showed that among four sets of attributions (namely computer usage attitudes, learning motivation, perception of satisfaction and previous academic performance), only previous academic performance exhibited a strong correlation with dropout [21]. Research by Zhang et al used multivariate regression to analyze the data of 57,549 students from nine universities: results showed that demographic attributions such as gender, ethnicity and nationality attribution are significantly correlated to dropping out [22]. Another logistic regression study conducted by Doherty analyzed the data of 10,466 students in the educational institution information system; results showed that the students' demographic attributions, learning methods, and curriculum interaction were correlated to dropping out [23].…”
Section: B Empirical Researchmentioning
confidence: 99%
“…Consequently, a clear focus has been directed towards early identification and diagnosis of at-risk students, and a variety of studies using statistical methods, data ISSN 1929-7750 (online). The Journal of Learning Analytics works under a Creative Commons License, Attribution -NonCommercial-NoDerivs 3.0 Unported (CC BY-NC-ND 3.0) mining, and machine learning techniques can be found in recent literature (Thammasiri, Delen, Meesad, & Kasap, 2013;DeBerard, Spielmans, & Julka, 2004;Zhang, Anderson, Ohland, & Thorndyke, 2004;Burtner, 2005;Yu, DiGangi, Jannasch-Pennell, Lo, & Kaprolet, 2007;Mendez, Buskirk, Lohr, & Haag, 2008;Li, Swaminathan, & Tang, 2009;Lin, Imbrie, & Reid, 2009;Delen, 2010;Zhang, Oussena, Clark, & Hyensook, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Viewing other factors through the lens of this framework might help explain some of the inconsistencies found in the previous research on engineering retention (see Zhang et al 46 for an example). Examples of factors that could be investigated with respect to the framework include: ethnicity, self-esteem, social integration into engineering, what influenced students to study engineering, time spent on classwork and studying, student participation in high school activities related to engineering, when students became interested in engineering, and beliefs on effort and intelligence.…”
Section: Resultsmentioning
confidence: 99%